Strategi Pencegahan Ekstremisme Berbasis Kekerasan Yang Mengarah Pada Terorisme Dalam Proyek Strategis Nasional - Rohmah Dwi Cahyaningsih; Febrian Halomoan; Slamet Tri Wahyudi (Journal of Innovative and Creativity, 2025)
The government has formulated policies to improve and equalize development through National Strategic Projects (PSN). The purpose of this paper is to analyze the conflicts arising from PSN that have the potential to cause violence-based extremism leading to terrorism, and to formulate strategies to overcome them. This paper uses a legislative and case study approach. The results of this study show that there are negative impacts arising from the implementation of PSN that threaten the economy, the right to life, and the existence of local communities. Economic inequality and discrimination against residents in PSN locations have the potential to lead to violent extremism. The government has issued Presidential Regulation No. 7 of 2021 concerning the National Action Plan for the Prevention of Violence-Based Extremism Leading to Terrorism (RAN PE) as an effort to counter terrorism. RAN PE serves as a guide for cross-sectoral coordination between various institutions in countering violent extremism. RAN PE can be implemented to prevent the potential for violent extremism in PSN areas. The strategy for preventing violent extremism leading to terrorism is to integrate human security and increase the resilience of vulnerable groups to acts of violent extremism through local economic empowerment. As a basis for future policy, the BNPT and related institutions need to create pilot areas and provide assistance in preventing extremism focused on PSN locations.